1997
DOI: 10.1111/j.1468-3083.1997.tb00487.x
|View full text |Cite
|
Sign up to set email alerts
|

Selective heat therapy in cutaneous leishmaniasis: a preliminary experience using the 585 nm pulsed dye laser

Abstract: Aim The purpose of this paper is to examine the effect of the yellow pulsed dye laser on the natural history of cutaneous leishmaniasis {CL). Materials and methodsA 31 year old Saudi patient suffered from CL due to L. trnpica. He was treated with 585 nm, 450 fis flashlamp pulsed dye (FLPD) laser. The patient received two laser sessions, 2 weeks apart using 5 mm spot size with a fleunce range of 8-8.5 J/cm~.Results The lesion healed completely within 6 weeks with hyperpigmentation. At 16 weeks, the ,skin exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…If one assumes that patients lost to follow-up during treatment experienced cure, the cure rate among patients treated with intralesional SSG would be significantly larger than that for patients treated with intramuscular SSG or with thermotherapy; the cure rates in the latter 2 groups would not differ significantly (table 3). Laboratory studies showed that Leishmania parasites do not readily multiply in macrophages at temperatures >39°C in vitro [20][21][22][23]. Specifically, 3 studies suggested that thermotherapy with radio-frequency waves could be effective for CL treatment.…”
Section: Discussionmentioning
confidence: 99%
“…If one assumes that patients lost to follow-up during treatment experienced cure, the cure rate among patients treated with intralesional SSG would be significantly larger than that for patients treated with intramuscular SSG or with thermotherapy; the cure rates in the latter 2 groups would not differ significantly (table 3). Laboratory studies showed that Leishmania parasites do not readily multiply in macrophages at temperatures >39°C in vitro [20][21][22][23]. Specifically, 3 studies suggested that thermotherapy with radio-frequency waves could be effective for CL treatment.…”
Section: Discussionmentioning
confidence: 99%